2017
DOI: 10.1103/physreve.95.022131
|View full text |Cite
|
Sign up to set email alerts
|

From maximum power to a trade-off optimization of low-dissipation heat engines: Influence of control parameters and the role of entropy generation

Abstract: For a low-dissipation heat engine model we present the role of the partial contact times and the total operational time as control parameters to switch from maximum power state to maximum Ω trade-off state. The symmetry of the dissipation coefficients may be used in the design of the heat engine to offer, in such switching, a suitable compromise between efficiency gain, power losses, and entropy change. Bounds for entropy production, efficiency, and power output are presented for transitions between both regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…This suggests that reaching η C at P > 0 may not be the holy grail of engineering practice where a tradeoff between power and efficiency is often optimized [41][42][43][44][45][46][47][48]. Consider for example the target function ξ = η α P β , α ≥ 0, β ≥ 0, which should be optimized.…”
Section: Bounds On Maximum Efficiency At Given Powermentioning
confidence: 99%
“…This suggests that reaching η C at P > 0 may not be the holy grail of engineering practice where a tradeoff between power and efficiency is often optimized [41][42][43][44][45][46][47][48]. Consider for example the target function ξ = η α P β , α ≥ 0, β ≥ 0, which should be optimized.…”
Section: Bounds On Maximum Efficiency At Given Powermentioning
confidence: 99%
“…The dot denotes the quantity per unit time for steady-state heat devices or the quantity divided by one cycle time for cyclic heat devices. Several models of heat devices were studied under the maximumΩ criterion [44,45,46,47,48,49,50,51,52,53,54] and found that the efficiency under the maximumΩ criterion, η(Ω max ), lies between the maximum efficiency and the efficiency at maximum power output i.e., η max > η(Ω max ) > η(P max ) [43]. The efficiency of a linear irreversible heat engine working at maximum power is bounded below half of the Carnot efficiency and reaches η C /2 under the tightcoupling condition.…”
Section: Introductionmentioning
confidence: 99%
“…For more details about the usefulness ofΩ criterion can be seen in Refs. [43,48,49,51,54]. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the CA-efficiency is recovered in the LD-model under the assumption of symmetric dissipation. Recently, a description of the LD model in terms of characteristic dimensionless variables was proposed in [40][41][42]. From this treatment, it is possible to separate efficiency-power behaviors typical of CA-endoreversible engines as well as irreversible engines according to the imposed time constraints.…”
Section: Introductionmentioning
confidence: 99%